Soxhlet Extraction versus Hydrodistillation Using the Clevenger Apparatus: A Comparative Study on the Extraction of a Volatile Compound from Tamarindus indica Seeds - Kehinde Oluwakemi Fagbemi; Daniel Ayandiran Aina; Olufunmiso Olusola Olajuyigbe (The Scientific World Journal)
The present study aims to compare two traditional extraction techniques. A volatile compound from Tamarindus indica seed was obtained with Soxhlet extraction (SE) and hydrodistillation using the Clevenger apparatus (HDC). The extraction yield and chemical composition of the essential oil samples were compared. Both oils extracted were analyzed with GC-MS, and forty-one chemical compounds were identified in essential oil components from SE while forty chemical compounds were found in the HDC-extracted oil sample. The major essential oil components present in both the SE and HDC method are cis-vaccenic acid, 2-methyltetracosane, beta-sitosterol, 9,12-octadecadienoic acid (Z, Z)-, and n-hexadecanoic acid in varying concentrations. Moreover, the essential oils obtained by both methods look similar quantitatively but differ qualitatively. The HDC method produced more oxygenated compounds that contribute to the fragrance of the oil. The major constituents observed in the essential oil extracted by SE methods include cis-vaccenic acid (17.6%), beta-sitosterol (12.71%), 9,12-octadecadienoic acid (Z, Z)- (11.82%), n-hexadecanoic acid (8.16%), 9,12-octadecadienoic acid, methyl ester (5.84%), oleic acid (4.54%), and 11-octadecenoic acid and methyl ester (3.94%). However, in the hydrodistillation technique, the oil was mostly composed of 9,12-octadecadienoic acid (Z, Z)- (23.72%), cis-vaccenic acid (17.16%), n-hexadecanoic acid (11.53%), beta-sitosterol (4.53%), and octadecanoic acid (3.8%). From the data obtained, HDC seems to be a better method for extraction of Tamarindus indica essential oil compared to the Soxhlet extraction apparatus.